2002
DOI: 10.1002/mc.10056
|View full text |Cite
|
Sign up to set email alerts
|

Induction of caspase‐mediated apoptosis and cell‐cycle G1 arrest by selenium metabolite methylselenol

Abstract: Previous work based on mono-methyl selenium compounds that are putative precursors of methylselenol has strongly implicated this metabolite in the induction of caspase-mediated apoptosis of human prostate carcinoma and leukemia cells and G1 arrest in human vascular endothelial and cancer epithelial cells. To test the hypothesis that methylselenol itself is responsible for exerting these cellular effects, we examined the apoptotic action on DU145 human prostate cancer cells and the G1 arrest effect on the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 16 publications
1
67
1
1
Order By: Relevance
“…2 (adapted from Combs, 2001;Rayman, 2004), from which it can be seen that CH 3 SeH can be formed by the methylation of H 2 Se as part of the Se excretory pathway. There is also some evidence that CH 3 SeH can be formed directly from selenomethionine either by the action of a g-lyase, also known as methioninase (Nakamuro et al 1997;Wang et al 2002;Spallholz et al 2004) or by an a, g-elimination reaction (Okuno et al 2005). Alternatively, it can be formed from a storage form of Se, i.e.…”
Section: Methyl Selenol and Its Precursorsmentioning
confidence: 99%
“…2 (adapted from Combs, 2001;Rayman, 2004), from which it can be seen that CH 3 SeH can be formed by the methylation of H 2 Se as part of the Se excretory pathway. There is also some evidence that CH 3 SeH can be formed directly from selenomethionine either by the action of a g-lyase, also known as methioninase (Nakamuro et al 1997;Wang et al 2002;Spallholz et al 2004) or by an a, g-elimination reaction (Okuno et al 2005). Alternatively, it can be formed from a storage form of Se, i.e.…”
Section: Methyl Selenol and Its Precursorsmentioning
confidence: 99%
“…Methylselenocysteine (MSC), a stable, water-soluble Se-compound that is quantitatively absorbed when taken orally [18], is then hydrolyzed by a β-lyase to yield methylselenol [2,10,19].…”
Section: Introductionmentioning
confidence: 99%
“…Selenium intervenes with two hallmarks of cancer: apoptosis and angiogenesis. Studies have shown that selenium compounds, most likely CH 3 SeH, can induce caspasemediated apoptosis in cancer cells (37)(38)(39). Angiogenesis is affected by CH 3 SeH precursors because of its inhibition of VEGF from several cancer cell lines (40).…”
mentioning
confidence: 99%